Antioxidant Activity Test of Sungkai Leaf (Peronema canescens Jack) Steeping Drink with the Addition of Honey - Febrining Tias; Arif Sabta Aji; Ryan Salfarino; Veriani Aprilia (Journal of Global Nutrition, 2022)
Background : Herbal Medicine in Indonesia have about 1,260 species in total. Mostly, many of the Indonesian from South Sumatra, use the sungkai plant (Peronema canescens Jack) to increase the body's immunity by making steeping drinks. Sungkai plants have secondary compounds such as alkaloids, flavonoids, and tannins which has function as antioxidants. The addition of honey as an alternative sweetener can be used to enhance the taste and also as an additional antioxidant.Objectives : This study aims to determine the antioxidant activity of sungkai leaf steeping drink with the addition of honey.Methods: This study was an experimental design and conducted in September-October 2021 at the Alma Ata University Food Laboratory and the Chemix Pratama Laboratory. Antioxidant activity analysis used the Dephenyl Picrylhydazil (DPPH) test on sungkai leaf steeping with the addition of honey. Fully randomized design and quantitative descriptive analysis with one-way ANOVA followed by Duncan's test.Results : Sungkai leaf steeping drink was tested for antioxidant activity to obtain an IC 50 value. In the control group (F0) without the addition of honey yield an IC50 value of 10,626.62 ppm, in the F1 treatment group with 1 g of Sungkai leaves and 8 ml of honey yield an IC50 value of 8,397.31 ppm, in the F2 treatment group with 1g of sungkai leaves and 10 ml of honey yield an IC50 value of 7,795.69 ppm, in the F3 treatment group with 2 g of sungkai leaves and 8 ml of honey yield an IC50 value of 8,189.88 ppm and in F4 treatment group 2 g of sungkai leaves and 10 ml honey yield an IC50 value is 7390.23 ppm. The F4 treatment group had the highest antioxidant activity with an IC50 value of 7,390.23 ppm.Conclusion : Steeping Sungkai leaf drink has antioxidant activity, however in very weak status. Further research needs to be done by modifying additional component to increase antioxidant activity in sungkai leaf steeping drinks.